Study of tool wear and surface roughness in machining of homogenised SiC-p reinforced aluminium metal matrix composite - Kiliçkap, E; Çakir, O; Aksoy, M; Inan, A (Elsevier Science Sa, 2005)
Metal matrix composites (MMC) have become a large leading material in composite materials and particle reinforced aluminium MMCs have received considerable attention due to their excellent engineering properties. These materials are known as the difficult-to-machine materials, because of the hardness and abrasive nature of reinforcement element like silicon carbide (SiC) particles. In this study, homogenised 5% SiC-p aluminium MMC material was selected for experimental investigation of tool wear and surface roughness. Two types of K10 cutting tool (uncoated and TiN-coated) were used at different cutting speeds (50, 100 and 150 m/min), feed rates (0.1, 0.2 and 0.3 mm/rev) and depths of cut (0.5, 1 and 1.5 mm). In dry turning condition, tool wear was mainly affected by cutting speed, increased with increasing cutting speed. Tool wear was lower when coated cutting tool was used in comparison to uncoated one. Surface roughness influenced with cutting speed and feed rate. Higher cutting speeds and lower feed rates produced better surface quality. (c) 2005 Elsevier B.V. All rights reserved.
8th International Conference on Advances in Materials and Processing Technologies/13th International Conference on Achievements in Mechanical and Materials Engineering -- MAY 16-19, 2005 -- Gliwice Wisla, POLAND
Keywords: metal matrix composites; machining; tool wear; surface roughness